James Gould Cozzens. - Hicks, Granville, 1901-1982 (University of Minnesota pamphlets on American writers ;, 1966)
James Gould Cozzens - American Writers 58 was first published in 1966. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.